Microbiological analysis of skin lesions of cod (Gadus morhua) from the southern part of the Baltic Sea - Pękala-Safińska Agnieszka; Nadolna-Ałtyn Katarzyna; Różycki Mirosław; Paździor Ewa; Cencek Tomasz; Podolska Magdalena (Journal of Veterinary Research, 2024)
Since the middle of the 1980s, severe skin disorders have been observed in Baltic cod (Gadus morhua) each year. Available data on the spectrum of bacteria isolated from the clinical cases being limited, and evaluation of the microbial background of fish skin lesions being useful, a bacteriological examination has been undertaken.